The Impact of Labour Market Dynamics on the Return-Migration of Immigrants - Govert E. Bijwaard; Christian Schluter; Jackline Wahba (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2012)
Using administrative panel data on the entire population of new labour immigrants to The Netherlands, we estimate the causal effects of individual labour market spells on immigration durations using the 'timing-of-events' method. The model allows for correlated unobserved heterogeneity across migration, unemployment and employment processes. We find that unemployment spells increase return probabilities for all immigrant groups, while re-employment spells typically delay returns. The precise quantitative impacts on migration durations depend on both the timing and lengths of the employment and unemployment spells, and are evaluated in several factual and counterfactual examples.
Keywords: J61; J64; C41; 330; temporary migration; durations; timing of event method; labour market dynamics